DeltaRex-G, tumor targeted retrovector encoding a CCNG1 inhibitor, for CAR-T cell therapy induced cytokine release syndrome - Haroun, Grace; Gordon, Erlinda M. (Frontiers in Molecular Medicine, 2024)
Cytokine release syndrome is a serious complication of chimeric antigen receptor-T cell therapy and is triggered by excessive secretion of inflammatory cytokines by chimeric T cells which could be fatal. Following an inquiry into the molecular mechanisms orchestrating cytokine release syndrome, we hypothesize that DeltaRex-G, a tumor targeted retrovector encoding a cytocidal CCNG1 inhibitor gene, may be a viable treatment option for corticosteroid-resistant cytokine release syndrome. DeltaRex-G received United States Food and Drug Administration Emergency Use Authorization to treat Covid-19-induced acute respiratory distress syndrome, which is due to hyperactivated immune cells. A brief administration of DeltaRex-G would inhibit a certain proportion of hyperactive chimeric T cells, consequently reducing cytokine release while retaining chimeric T cell efficacy.